JAK inhibitors in systemic juvenile idiopathic arthritis - He, Tingyan; Xia, Yu; Luo, Ying; Yang, Jun (Frontiers in Pediatrics, 2023)
Objective Systemic juvenile idiopathic arthritis (SJIA) is characterized by excessive and inappropriate production of proinflammatory cytokines. Janus kinase inhibitors (JAKi) can block the downstream pathway of many cytokines. The use of JAKi in SJIA or macrophage activation syndrome (MAS) has only been described in a limited number of case reports. In this study, we aimed to assess the efficacy and potential adverse effects of JAKi in SJIA patients. Methods Patients with SJIA who received JAKi and underwent at least one assessment of efficacy and safety after JAKi initiation were eligible for this study. Data were collected retrospectively from inpatient or outpatient medical records at JAKi initiation, at 1, 3, 6, 9, and 12 months, after disease flare, after JAKi discontinuation, or at the last follow-up. Results Ten patients with SJIA were included in the study. At the start of JAKi treatment, all patients presented with active disease; five showed variable adverse effects secondary to glucocorticoids. Seven patients received tofacitinib (one later switched to ruxolitinib). Of these, only two patients showed a complete response of persistent arthritis associated with tocilizumab; tofacitinib was used without a biological DMARD only in two patients, together with MTX, showing a partial response; three patients were nonresponders. Four patients with SJIA-related MAS or persistent hyperferritinemia were treated with ruxolitinib. Ruxolitinib allowed a good response on MAS parameters in three of them. All these four patients required an adjunction or switch to canakinumab later. The median decrease in the daily glucocorticoid dose between JAKi initiation and the last follow-up was 90.6% in patients with complete remission and 77.4% in other patients. Three patients discontinued glucocorticoid treatment after the introduction of JAKi. Severe adverse events, notably serious infection or thrombosis, were not observed during JAKi treatment. Conclusion JAKi may be an alternative or adjuvant agent for SJIA patients, especially in those with persistently active disease, glucocorticoid-related adverse reactions, or SJIA-MAS.